STRATEGI PENINGKATAN INDEKS SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK KOTA BEKASI - Irwansyah, Iwan - (Universitas Gajah Putih, 2023)
The government realizes the important role of SPBE to support all development sectors. Efforts to encourage the implementation of SPBE have been made by the government by issuing laws and regulations which mandate the need for the implementation of information systems or SPBE. So far, ministries, institutions and regional governments have implemented SPBE individually according to their capacity, and achieved levels of SPBE progress that vary widely nationally. To build synergy in the implementation of SPBE that has legal force between ministries, institutions and regional governments, a National SPBE Master Plan is needed which is used as a guide for Central Agencies and Regional Governments to achieve an integrated SPBE. Research is carried out using a descriptive method which attempts to describe the object or subject as it is, with the aim of accurately describing the facts and characteristics of the object being studied. To obtain the required data, quantitative data is needed and interviews with related parties are then analyzed. Electronic Based Government (SPBE) has become an obligation of Regional Governments based on Presidential Regulation no. 95 of 2018 concerning Electronic Based Government Systems. For the City of Bekasi, the elaboration has been regulated in Regulation Number: 555.10/Kep.233 Diskominfostandi/VI/2022 CONCERNING the Electronic-Based Government System Master Plan, Based on the results of the evaluation of the Ministry of PAN and RB of the Bekasi City SPBE Index by looking at 47 indicators based on Permenpan RB no. 59 of 2020, in 202 the value was 2.94, in 2022 the value was 2.78, this was caused by several things, including: the Master Plan or SPBE master plan, which was only determined in 2022 in June 2022, Human Resources Support in Regional Apparatus Organizations has not been maximized which is actually capable of creating IT applications in providing services to the community. Application usage is not optimal, and some cannot be traced. Weaknesses in implementing SPBE in the city of Bekasi in terms of governance and management. Budget support is not yet optimal for each Regional Apparatus organization in developing IT applications. The team that has been formed and chaired by the Regional Secretary has not been able to collaborate in implementing ICT to achieve a Smart City.